2000
DOI: 10.1530/eje.0.1420294
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenic acute regulatory protein mRNA expression in adrenal tumours

Abstract: The rate limiting step in steroidogenesis is cholesterol transport through the outer to the inner mitochondrial membrane and the cytochrome P450 side chain cleavage (P450scc) complex. The protein factor responsible for this transport, and as such necessary for regulating the acute production of steroids, has been identified and named the steroidogenic acute regulatory protein (StAR). We investigated the expression of StAR in functional and non-functional adrenal neoplasms and compared the expression with that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…These results are in a good agreement with previously reported effects of forskolin stimulation in primary adrenal as well as in NCI-H295R cells (3,5,9,15). Stimulation of NCI-H295R cells with forskolin induced a 1.5-fold increase in StAR mRNA (21). Bird et al (4) reported an increase in the expression of CYP21A2, CYP17, CYP11A1, CYP11B1, and CYP11B2 enzymes by forskolin as well as by dibutyrylcAMP.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in a good agreement with previously reported effects of forskolin stimulation in primary adrenal as well as in NCI-H295R cells (3,5,9,15). Stimulation of NCI-H295R cells with forskolin induced a 1.5-fold increase in StAR mRNA (21). Bird et al (4) reported an increase in the expression of CYP21A2, CYP17, CYP11A1, CYP11B1, and CYP11B2 enzymes by forskolin as well as by dibutyrylcAMP.…”
Section: Discussionsupporting
confidence: 91%
“…The protein responsible for this transport, and as such regulating the acute production of steroids, has been identified and named steroidogenic acute regulatory protein (StAR) (21).…”
mentioning
confidence: 99%
“…43 Despite its critical role, the expression of StAR shows only small variations among the different types of adrenal tumors, including APA, cortisolproducing adenomas, and nonfunctional adenomas, compared with normal adrenal. 37,44 Overexpression of the high-density lipoprotein scavenger receptor B1 suggests that cholesterol supply to the cell is increased through the high-density lipoprotein pathway; increases in adrenodoxin and P450 oxidoreductase indicate that additional electrons are provided via these 2 pathways to both mitochondrial P450 enzymes and enzymes located in the endoplasmic reticulum 38 (Table 1). Assié et al 38 showed that several genes involved in calcium signaling were differently expressed between control adrenal and APA, particularly the calcium effector calmodulin and genes encoding proteins involved in calcium storage, that is, the endoplasmic reticulum calreticulin and the calcium ATPase SERCA3.…”
Section: Intracellular Signaling and Transcriptional Regulationmentioning
confidence: 99%
“…Whether the excess aldosterone in APA depends on aberrant StAR gene expression and/or upregulated activity by posttransductional mechanisms, as phosphorylation of regulatory residues, is unclear, because data in APA are limited and conflicting. 13,14 Hence, given the complexity of these molecular pathways, we used a whole transcriptome analysis approach to gain insight into the mechanisms causing aldosterone excess in APA.…”
mentioning
confidence: 99%